Implementasi Kebijakan Jogo Tonggo Dalam Penanganan Pandemi COVID-19 Di Desa Temulus Kecamatan Mejobo Kabupaten Kudus Tahun 2021 - Sari, Hendiyati Paulina; Ni’am, Harun (Fakultas Ilmu Sosial dan Ilmu Politik Unwahas, 2022)
This study aims to describe the process of implementing the jogo tonggo policy in handling the Covid-19 pandemic in Temulus Village, Mejobo District, Kudus Regency and to describe the supporting factors and obstacles to the implementation of the jogo tonggo policy in Temulus Village. By using descriptive qualitative research methods. The results of the research conducted showed that the implementation of the jogo tonggo policy in handling the Covid-19 pandemic in Temulus Village which was analyzed using Edward III's implementation theory which consisted of 4 (four) variables, namely communication, resources, disposition and bureaucratic structure had gone well in accordance with existing guidelines or SOPs. The supporting factors for this policy are support and good coordination between all elements, including the Temulus Village Government, the Jogo Tonggo Task Force, and the community, and a clear and well-structured division of tasks. However, in its implementation there are still inhibiting factors such as inadequate facilities, limited budget, lack of implementing incentives, and social sanctions that are still not firm from policy makers.